Coke Slurries with Improved Higher Heating Value and Good Processability via Particle Shape Design. Issue 10 (31st August 2017) - Jampolski, Leon; Jakobs, Tobias; Kolb, Thomas; Willenbacher, Norbert
Abstract: Coke‐water slurries can be used as biogenic intermediates in conversion of residual biomass into high value fuels such as liquefied petroleum gas or synthetic natural gas. The effect of particle size and shape on the flow behavior of slurries including coke particles obtained from fast pyrolysis was investigated. Particles were shaped in a planetary ball mill and equivalent sphere diameter and circularity were used to characterize size and shape. An increased circularity resulted in a strong decrease in slurry viscosity. Accordingly, a higher mass fraction of particles can be mixed into the slurry, thus, increasing the higher heating value while still preserving good processing properties. Abstract : The effect of particle size and shape on the flow behavior of carbonaceous slurries is investigated. With increasing circularity, as obtained by particle milling, a strong decrease of slurry viscosity is achieved. Accordingly, a higher mass fraction of the treated particles can be mixed into the slurry, thus, increasing the higher heating value while still preserving good processing properties.